Importance of phosphoinositide binding by human β‐defensin 3 for Akt‐dependent cytokine induction. Issue 1 (15th December 2017) - Phan, Thanh Kha; Lay, Fung T; Hulett, Mark D
Abstract: Host defense peptides (HDPs) are well‐characterized for their antimicrobial activities but also variously display potent immunomodulatory effects. Human β‐defensin 3 (HBD‐3) belongs to a well‐known HDP family known as defensins and is able to induce leukocyte chemotactic recruitment, leukocyte activation/maturation, proinflammatory cytokine release, and co‐stimulatory marker expression. HBD‐3‐stimulated cytokine induction is NF‐κB‐dependent and was initially suggested to act via G protein‐coupled C‐C chemokine receptor phospholipase C (PLC) and/or Toll‐like receptor signaling. Subsequent pharmacological inhibition, however, revealed that NF‐κB activation by HBD‐3 is receptor‐independent and instead involves the phosphoinositide 3‐kinase (PI3K)‐protein kinase B (Akt) pathway, the mechanism of which remains undetermined. Recently, we have shown that HBD‐3 can enter mammalian cells and bind to inner membrane phosphoinositide 4, 5‐bisphosphate [PI(4, 5)P2 ], an important second lipid messenger of PLC and PI3K‐Akt pathways. In this study, we report that the interaction of HBD‐3 with PI(4, 5)P2 is important for PI3K‐Akt‐NF‐κΒ‐mediated induction of tumor necrosis factor and interleukin‐6. These data provide insights into the mechanism of immunomodulation by HBD‐3, and more generally, highlight the complex multifaceted signaling roles of HDPs in innate defense. Furthermore, it is suggested that the proposed mode of action may be conserved in other HDPs. Abstract : Human β‐defensin 3 (HBD‐3) is an important immunomodulatory host defense peptide (HDP). In this study, we identify a direct interaction of HBD‐3 with the cellular phospholipid PI(4, 5)P2 as an important mechanism in cytokine induction by monocytes. We show that HBD‐3 is internalized by monocytes and its subsequent binding to PI(4, 5)P2 activates the PI3K‐Akt‐NF‐κB pathway to induce tumor necrosis factor and IL‐6; a process that highlights the multifaceted signaling roles of HDPs in innate immunity.